In-situ monitoring of temperature distribution in operating solid oxide fuel cell cathode using proprietary sensory techniques versus commercial thermocouples. (15th November 2018) - Guk, Erdogan; Kim, Jung-Sik; Ranaweera, Manoj; Venkatesan, Vijay; Jackson, Lisa
Highlights: A physical sensor is placed directly onto solid oxide fuel cell electrode. Temperature increment (0.4–3 °C) was monitored locally with varying fuel flow rate. Respective contributions of gas cooling, starvation and electrochemical activity investigated. The sensor presents higher temporal and spatial resolution than conventional TCs. All experimentally measured data were validated with theoretical calculations. Abstract: Real time surface temperature distribution monitoring of Solid Oxide Fuel Cell (SOFC) systems is important to identify temperature related degradation and understand cell performance. This type of monitoring is limited due to the harsh operating environment of SOFC. Therefore, the temperature variation of an operating SOFC is generally predicted by applying modelling tools which take into account the conventional I-V (current (I)-voltage (V)) curve. However, experimentally obtained temperature data is vital for management of high temperature related degradation and for more reliable modelling of the SOFC. In this study, the temperature distribution of the SOFC is in-situ monitored along the entire cell cathode simultaneously, using commercial TCs on the gas flow channel (the present conventional method) alongside the in-house-developed sensor sensing points (SSPs) directly from the cell cathode surface under both open circuit voltage (OCV) and loading conditions. A considerable difference is observed, especially under the loading condition, between the temperature obtained from the TCs and SSPs even from the same locations. Furthermore, the contribution(s) of different parameters on the temperature variation are investigated, including fuel/air amount under OCV, gas cooling effect, contact area effect and flow direction effect under the loading condition for the given SOFC. There is a fivefold increase in spatial resolution, alongside higher temporal resolution, being observed with the implemented sensor compared to the resolution obtained from the conventional TCs, which yields promise for further development and investigation into test cells and stacks.